FAKTOR-FAKTOR YANG MEMOTIVASI PETANI DALAM MELAKUKAN USAHATANI SEMANGKA (Citrullus vulgaris S.) DI DESA SUMBER SARI KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA (Factors Motivating Farmers in Watermelon Farming (Citrullus vulgaris S.) in Sumber Sari Village, Kota Bangun Subdistrict, Kutai Kartanegara District) - MUHAMMAD RAMADHANI ARDI; MIDIANSYAH EFFENDI (Universitas Mulawarman (University of Mulawarman), 2018)
The purpose of this research was to know factors motivating farmers in watermelon farming in Sumber Sari Village, Kota Bangun Subdistrict, Kutai Kartanegara District. This research was carried out during 6 months from May to November 2017. The number of samples used in this study was as many as 32 watermelon farmers. Data analysis used multiple linear regression. The result of this research showed the age, education, land area, and the number of dependants simultaneously affect the motivation of farmers in watermelon farming. Age and education do not partially affect the motivation of watermelon farmers, while the land area and number of dependents partially affect the motivation of watermelon farmers.